Analisis Fundamental Makro, Fundamental Mikro Terhadap Kinerja Keuangan dengan Pangsa Pasar, Struktur Kepemilikan dan Karakteristik Perusahaan pada Perusahaan Rokok yang Terdaftar di Bursa Efek Indonesia pada Tahun 2011-2020 - Laila, Amar’atus; Hwihanus (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
An abstract is often presented separate from the article, so it must be able to stand alone. A well-prepared abstract enables the reader to identify the basic content of a document quickly and accurately, to determine its relevance to their interests, and thus to decide whether to read the document in its entirety. The abstract should be informative and completely self-explanatory, provide The purpose of this research is to analyze the macro and micro fundamentals of financial performance as well as market share, company characteristics and structure of cigarette companies on the Indonesia Stock Exchange from 2011 to 2020. The analysis of this research is quantitative research with data on independent variables and dependent variables. Data comes from BEI reports and website. The sample used was 30 cigarette companies on the Indonesian Stock Exchange. Using the data analysis method, namely PLS version 4. The results of the proposed hypothesis show that 6 independent variables have a positive and significant effect on the dependent variable, while the remaining 7 variables have a negative effect on the dependent variable, namely financial performance.